Analisis Penerapan Akuntansi Lingkungan Dalam Pengelolaan Sampah Pada TPST Kesiman Kertalangu Di Kota Denpasar - I Gusti Ayu Merry Riska Wulandari; Kadek Dewi Padnyawati Wulandari (Hita Akuntansi dan Keuangan, 2026)
This study aims to evaluate the implementation of environmental accounting in waste management activities at TPST Kesiman Kertalangu in Denpasar City. The research uses a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings indicate that environmental accounting practices at the facility have not yet been implemented systematically. Environmental costs, including prevention costs, detection costs, internal failure costs, and external failure costs, have been identified by management. However, these costs are still combined with general operational expenses and are not recorded separately in financial reports. This condition makes it difficult to assess environmental performance accurately and effectively. In terms of recognition and measurement, the TPST has applied accounting principles using the historical cost approach. Nevertheless, the presentation and disclosure of environmental costs remain inadequate because they are not specifically disclosed in financial statements. The study also found several major obstacles, such as limited human resources, the absence of specific regulations, and the use of simple accounting information systems. Therefore, this research recommends developing a more structured environmental cost classification system and improving environmental reporting practices to support transparency, accountability, and sustainable waste management in the future.